Whose reality?: challenges and prospects posed by Dembare dotcoms to the traditional practise of football reporting in Zimbabwe - Kaserera, Marcia (Midlands State University, 2017)
Before the advent of the internet, the mainstream media in Zimbabwe and across the globe, enjoyed the privilege of mediating and interpreting football ‘reality’ to the audiences. This ‘privilege’ to mediate reality and the traditional practice of sports reporting in general, is undeniably under threat in this internet age. Academic studies focusing on the influence of internet sites such as Facebook, have overlooked how internet has affected the sport reporting landscape. This study located in the interpretive prism of qualitative paradigm of research, makes a ‘thick description’ (see Geertz 1973) of Zimbabwe sports journalists’ experiences and perceptions of DeMbare DotComs, a vibrant Facebook page for Dynamos fans. The intention was to find out how DeMbare DotComs, has affected the way sports journalists mediate and interpret football ‘reality’ to the audiences in Zimbabwe. Findings show that social (new) media network sites such as DeMbare DotComs has threatened and affected the traditional practice of football reporting in Zimbabwe. In actual fact sports journalists compete with DeMbare DotComs to break news and ‘scoops’ to the audiences. However, on a positive note DeMbare DotComs has also become a key site for sports diaries to some sports journalists.